Transfers between health facilities of people living with diabetes attending primary health care services in the Western Cape Province of South Africa: A retrospective cohort study - Odayar, Jasantha; Rusch, Jody; Dave, Joel A.; Van Der Westhuizen, Diederick J.; Mukonda, Elton; Lesosky, Maia; Myer, Landon (Tropical medicine & international health, 2024)
Objectives Transfers between health facilities of people living with HIV attending primary health care (PHC) including hospital to PHC facility, PHC facility to hospital and PHC facility to PHC facility transfers occur frequently, affect health service planning, and are associated with disengagement from care and viraemia. Data on transfers among people living with diabetes attending PHC, particularly transfers between PHC facilities, are few. We assessed the transfer incidence rate of people living with diabetes attending PHC, and the association between transfers between PHC facilities and subsequent HbA1c values. Methods We analysed data on HbA1c tests at public sector facilities in the Western Cape Province (2016–March 2020). Individuals with an HbA1c in 2016–2017 were followed‐up for 27 months and included in the analysis if ≥18 years at first included HbA1c, ≥2 HbA1cs during follow‐up and ≥1 HbA1c at a PHC facility. A visit interval was the duration between two consecutive HbA1cs. Successive HbA1cs at different facilities of any type indicated any transfer, and HbA1cs at different PHC facilities indicated a transfer between PHC facilities. Mixed effects logistic regression adjusted for sex, age, rural/urban facility attended at the start of the visit interval, disengagement (visit interval >14 months) and a hospital visit during follow‐up assessed the association between transfers between PHC facilities and HbA1c >8%. Results Among 102,813 participants, 22.6% had ≥1 transfer of any type. Including repeat transfers, there were 29,994 transfers (14.4 transfers per 100 person‐years, 95% confidence interval [CI] 14.3–14.6). A total of 6996 (30.1%) of those who transferred had a transfer between PHC facilities. Visit intervals with a transfer between PHC facilities were longer (349 days, interquartile range [IQR] 211–503) than those without any transfer (330 days, IQR 182–422). The adjusted relative odds of an HbA1c ≥8% after a transfer between PHC facilities versus no transfer were 1.20 (95% CI 1.05–1.37). Conclusion The volume of transfers involving PHC facilities requires consideration when planning services. Individuals who transfer between PHC facilities require additional monitoring and support.